2013
DOI: 10.1051/0004-6361/201321660
|View full text |Cite
|
Sign up to set email alerts
|

Study of the impact of the post-MS evolution of the host star on the orbits of close-in planets

Abstract: Context. More than 40 planets have been found around giant stars, revealing a lack of systems orbiting interior to ∼0.6 AU. This observational fact contrasts with the planetary population around solar-type stars and has been interpreted as the result of the orbital evolution of planets through the interaction with the host star and/or because of a different formation/migration scenario of planets around more massive stars. Aims. We are conducting a radial velocity study of a sample of 166 giant stars aimed at … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2014
2014
2015
2015

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 32 publications
1
29
1
Order By: Relevance
“…The resulting velocities are shown in Figure 1. The RMS around zero is ∼10 m s −1 , which is higher than the ∼ 4 m s −1 obtained by Jones et al (2013) for the same star, however the difference is due to the limited data used in their work that spanned just over 3 years and were observed after 2007. Prior to this date there was no standard calibration plan for FEROS, thus the wavelength solution was poorer.…”
Section: Radial Velocity Calculationcontrasting
confidence: 54%
See 2 more Smart Citations
“…The resulting velocities are shown in Figure 1. The RMS around zero is ∼10 m s −1 , which is higher than the ∼ 4 m s −1 obtained by Jones et al (2013) for the same star, however the difference is due to the limited data used in their work that spanned just over 3 years and were observed after 2007. Prior to this date there was no standard calibration plan for FEROS, thus the wavelength solution was poorer.…”
Section: Radial Velocity Calculationcontrasting
confidence: 54%
“…The RVs were computed in a similar way as described in Jones et al (2013), according to the following procedure. First, each order was separated into four chunks and the doppler shift was computed by applying a cross correlation (Tonry & Davis 1979) between the stellar spectrum and its corresponding template (high S/N spectrum of the same star).…”
Section: Radial Velocity Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…5 0± 0.21 2.42 ± 0.27 1.63 ± 0.22 R (R ) 8 . 9 3± 1.02 11.6 ± 1.4 5.92 ± 0.44 method (Baranne et al 1996), according to the method described in Jones et al (2013) and .…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…Based on this method, Jones et al (2013) showed that it is possible to reach a long-term precision of ∼3 m s −1 using FEROS data. The main steps of this method are described below.…”
Section: Radial Velocity Calculationsmentioning
confidence: 99%